q+xp-p2=0
"\\frac{\u2202f} {\u2202p}" =(x-2p)
"\\frac{\u2202f} {\u2202q}" =1
"\\frac{\u2202f} {\u2202x}" =p
"\\frac{\u2202f} {\u2202y}" =0
"\\frac{\u2202f} {\u2202z}" =0
"\\frac{dx} {(-\u2202f\/\u2202p)}" ="\\frac{dy} {(-\u2202f\/\u2202p)}" ="\\frac{dz} {(-p \u2202f\/\u2202p-q \u2202f\/\u2202q)}" =
"\\frac {dp} {(\u2202f\/\u2202x+p \u2202f\/\u2202z)}" +"\\frac{dq} {(\u2202f\/\u2202y+q \u2202f\/\u2202z)}" ="\\frac{(\u2202\u2205)} {0}"
"\\frac{dx} {(-(x-2p) )}" =
"\\frac{dy} {(-1)} =\\frac{dz} {(-p(x-2p)-q)} =\\frac{dp} {p} =\\frac{dq} {0} =\\frac{(\u2202\u2205)} {0}"
="\\frac {dy} {(-1)} =\\frac{dp} {p}"
log p=-y+log a
p=ae-y
q+xae-y=(ae-y)2
q=a2 e-2y-xae-y
dz=pdx+qdy
dz=ae-y dx+a2 e-2y-xae-y dy
dz=a e-y dx-xe-y dy)+a2 e-2y dy
Using −p(x−2p)−q=p2=a2e2y the z and p fractions combine to dz=pdp which integrates to
"z=axe^{-y}-\\frac{1}{2}a^2e^{-2y}+b"
Comments
Leave a comment